Improving Learning Outcomes Using Case Based Learning (CBL) Assisted by Interactive Videos on Optical Materials - Windrawan, I Gede; Muhyi, Abdul; Astra, I Made (Universitas PGRI Semarang, 2024)
This study examines the effectiveness of applying the Case Based Learning (CBL)Model assisted by interactive videos in improving students' cognitive learning outcomes onoptical materials. The method used is Classroom Action Research with the subject of grade XIMIPA 5 students at SMA Negeri 6 Tangerang Regency for the 2023/2024 school year. Thisresearch was carried out in three cycles, including planning, implementation, observation, andreflection. The results showed that implementing interactive video-assisted CBL significantlyimproved students' cognitive learning outcomes. The average cognitive score of studentsincreased from 55.6 in the first cycle, to 70.4 in the second cycle, and reached 75.2 in the thirdcycle. In addition, the success rate of classical learning also increased from 28.7% in the firstcycle to 79.7% in the third cycle. This improvement shows that interactive video-assisted CBLis effective in actively engaging students in learning, improving conceptual comprehension, andmotivating students to learn physics. This study suggests the application of interactive video-assisted CBL as an alternative learning method that can improve the quality of physics educationin schools.